THE RELATIONSHIP BETWEEN DIVIDEND PAYMENT AND EARNINGS QUALITY - Aaron Untung; Hanna Wijaya (Jurakunman (Jurnal Akuntansi dan Manajemen), 2019)
This research aims to examine the relationship between dividend payment and earnings quality. In this research, dividend paying status and dividend payout ratio which are features of dividend payment is used as the independent variables and the dependent variable is earnings quality. Earnings quality is measured by absolute value of discretionary accruals. The data in this research is collected from 97 companies from the manufacturing industry listed in the Indonesia Stock Exchange. The period of data collected was from 2013-2015. The research method used in this research is multiple regression where several classical assumption tests are conducted prior to find the result of the model using SPSS 21. The results in this research show that dividend paying status and dividend payout ratio have no significant association with earnings quality, hence there is no evidence of relationship between dividend payment and earnings quality Keywords: Dividend Paying Status (DPS), Dividend Payout Ratio (DPR), Earnings Quality (EQ) and Absolute value of Discretionary Accruals (ADA).